Study the Phased Equilibrium in the Binary Sentence )BaCl2-Na2CO3( (Latakia University Journal -Basic Sciences Series, 2021)
In this research, phase equilibrium is studied in the binary sentence (BaCl2-Na2CO3))transformations are common in nature, they have benefited from human in the development and improvement of old materials, from which he was able to navigate in the unfamiliar phase transformations (superfluids, superconductivity), which can solve many of the technical problems facing technology, and still this section Open as long as the will to improve life based on scientific progress exists.The importance of research is to obtain crystalline compounds in the binary sentences (BaCl2 –Na2CO3) because of these qualities of these salts in the fields of technology, so it was important to study the possibility of obtaining new phases at different molar ratios and draw schemes Its eccentric balances .In this study we prepare nine samples according to different molar ratios from tow compounds Soduim Carbonate  and Baruim Chloride and then mix the two materials with each other well, then the samples are prepared in the form of tablets after that we analysis this samples using the devices (XRD,DTA ,MP,EDX,SEM). This study shows the formation of a crystalline compound with the chemical formula( Ba6Na8Cl12C4O12) , and it also shows the formation of a solid solution on the basis of this compound, as Soduim Carbonate dissolves in the formed compound( Ba6Na8Cl12C4O12) .